Basal microvilli define the metabolic capacity and lethal phenotype of pancreatic cancer. Issue 3 (22nd January 2021) - Han, Xu; Ma, Lixiang; Gu, Jichun; Wang, Dansong; Li, Ji; Lou, Wenhui; Saiyin, Hexige; Fu, Deliang
Abstract: Apical microvilli of polarized epithelial cells govern the absorption of metabolites and the transport of fluid in tissues. Previously, we reported that tall and dense basal microvilli present on the endothelial cells of pancreatic cancers, a lethal malignancy with a high metabolism and unusual hypomicrovascularity, contain nutrient trafficking vesicles and glucose; their length and density were related to the glucose uptake of pancreatic cancers in a small‐scale analysis. However, the implications of basal microvilli on pancreatic cancers are unknown. Here, we evaluated the clinical implications of basal microvilli in 106 pancreatic cancers. We found that basal microvilli are a dominant change in pancreatic cancers. The presence of longer and denser basal microvilli on the microvessels in pancreatic cancer tissues positively correlated with increased glucose uptake and higher metastatic (or invasive) and proliferative potentials of neoplastic cells and vice versa. Clinically, postoperative patients with longer and denser basal microvilli were more prone to unfavorable pathological characteristics and dismal prognoses. They were even more refractory to adjuvant therapy than those with shorter and thinner basal microvilli were. Our findings show that basal microvilli define the metabolic capacity and lethal phenotype of pancreatic cancers. © 2020 The Authors. The Journal of Pathology published by John Wiley & Sons, Ltd. on behalf of The Pathological Society of Great Britain and Ireland.